Comparison of frictional pressure drop models during annular flow condensation of R600a in a horizontal tube at low mass flux and of R134a in a vertical tube at high mass flux - Dalkilic, A. S.; Agra, O.; Teke, I.; Wongwises, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
This study compares well-known two-phase pressure drop models with the experimental results of a condensation pressure drop of (I) R600a in a 1 m long horizontal smooth copper tube with an inner diameter of 4 mm, outer diameter of 6 mm and (II) R134a in a 0 5 m vertical smooth copper tube with an inner diameter of 8.1 mm and outer diameter of 9.52 mm. Different vapour qualities (0.45-0.9 for R600a and 0.7-0.95 for R134a), various mass fluxes (75-115 kg m(-2) s(-1) for R600a and 300-400 for R134a kg m(-2) s(-1)) and different condensing temperatures (30-43 degrees C for R600a and 40-50 degrees C for R134a) were tested under annular flow conditions. The quality of the refrigerant in the test section was calculated considering the temperature and pressure obtained from the experiment. The pressure drop across the test section was directly measured with a differential pressure transducer. The most agreeable correlations of various available options were then identified according to the results of analysis during annular flow regime (C) 2009 Elsevier Ltd All rights reserved.
Keywords: Condensation; Pressure drop; Horizontal flow; Downward flow; R600a; R134a; HEAT-TRANSFER COEFFICIENT; VOID FRACTION MODELS; 2-PHASE FLOW; FILM CONDENSATION; AIR-WATER; REFRIGERANTS; CHANNELS; MIXTURE; Thermodynamics; Engineering; Mechanics